Numerical approximation of plane deformation for the indentation of granular material by a smooth rigid wedge punch - Syafikah, Ayob; Nor Alisa, Mohd Damanhuri (Horizon Research Publishing, 2019)
In this paper, a numerical approximation of the stress equation for the indentation of granular materials by a smooth rigid wedge is presented. Plane strain conditions are assumed, and the materials obey the Mohr-Coulomb yield condition. This method determines the deformation of granular material under a smooth rigid wedge punch and construction of stress field in the deforming region which are presented by using MATLAB programme. The granular material is assumed to be in dense, solid like state. The solution only refers to the initial motion after the punch. This was then applied on one type of boundary value problem. By using MATLAB, the value of each point (x,y) and the stress variables (p,ψ) which construct the deformation field are calculated. This method provides simple and reliable algorithms for the solution of the deformation problems involving the stress variables. The results will consequently help in the improvement of the existing labs and experimental facilities in the industries and will eventually increase its efficiency.